Texture, Water Absorption, aw and Hedonic Quality Flakes White Millet (Panicum miliaceum) with Addition of Pumpkin Flour (Cucurbita moschata) - Sabrina Sabiella Husna; Antonius Hintono; Heni Rizqiati (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2020)
This research investigated the effect of pumpkin flour on texture, water absorption, aw, and hedonic quality of white millet flakes. The research design used Completely Randomized Design with one factor of pumpkin flour concentration. White millet, sugar, salt, and pumpkin flour were used as materials. Pumpkin flour was added to the flakes’ dough at a concentration of 0, 10, 20, and 30% (w/w). The results showed that the pumpkin flour provided a significant effect (p <0.05) to texture, water absorption, and hedonic quality of flakes, but did not provide significant affect (p> 0.05) to aw. The most optimal concentration of pumpkin flour was 10% proved by texture of 395 gf, water absorption of 95%, aw of0,25, and best organoleptic properties which were slightly yellow color, slightly fragrant aroma of pumpkin, a slight taste of pumpkin, and crispy texture. As conclusion, the utilization pumpkin flour to the dough may affected to the physical appearance in the flakes.